OPTIMIZING MAIL SERVER USING ZIMBRA COLLABORATION SUITE 5.0.2 IN OPERATING SYSTEM CENTOS 5.0 - Suprihatin, Ika Setiowati; Agushinta R, Dewi (Jurnal Ilmiah Informatika Komputer, 2009)
The idea of e-mail brings this world into the revolution in digital information. Today, e-mail is a communication media which is very popular. In order to send and receive e-mail, it needs a server which provide email service. This application usually calls Mail Transfer Agent (MTA). One of MTA that usually used is Zimbra. This research tries to implement and optimize the mail server Zimbra which install in operating system Centos 5.0. Testing of optimization is conducted by setting account in administration and makes a communication with e-mail.Keyword(s) : mail server, MTA, operating system, ZimbraSubject Description : H.4.Information System Applications | H.4.3. Communications Applications | Electronic Mail